1962
DOI: 10.1002/pol.1962.1205616408
|View full text |Cite
|
Sign up to set email alerts
|

The thermal degradation of some epoxy resins

Abstract: Studies on the thermal and oxidative polymer degradation have been presented in monographs by Grassie' and Jellinek.The general consensus in the majority of these studies is that thermal and oxidative degradation of polymers is a radical reaction. Unlike the case of degradation of polymer products, the thermal decomposition of condensation resins has received virtually no attention, despite the fact that these resins have been widely used up to the present time in industry.In the present work we have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 5 publications
3
22
0
Order By: Relevance
“…The alteration of the thermal parameters of the cured neat epoxy and nanocomposites in nitrogen or air was due to the fact that, in addition to the effects of high temperature, the existence of oxygen in air reacted with the epoxy chain through the oxidation reaction. This led to the breaking of the epoxy chain to form lower molecular weight substances (aldehydes, carbon dioxide, carbon monoxide, methane, propylene, and water) . According to Neman et al ., the oxidative decomposition of epoxy resins is an autocatalytic process and is superficially associated with the formation and the further degradation of peroxide compounds by a radical mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration of the thermal parameters of the cured neat epoxy and nanocomposites in nitrogen or air was due to the fact that, in addition to the effects of high temperature, the existence of oxygen in air reacted with the epoxy chain through the oxidation reaction. This led to the breaking of the epoxy chain to form lower molecular weight substances (aldehydes, carbon dioxide, carbon monoxide, methane, propylene, and water) . According to Neman et al ., the oxidative decomposition of epoxy resins is an autocatalytic process and is superficially associated with the formation and the further degradation of peroxide compounds by a radical mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…This led to the breaking of the epoxy chain to form lower molecular weight substances (aldehydes, carbon dioxide, carbon monoxide, methane, propylene, and water) . According to Neman et al ., the oxidative decomposition of epoxy resins is an autocatalytic process and is superficially associated with the formation and the further degradation of peroxide compounds by a radical mechanism. Xiaoxing et al .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that epoxies cured with meta ‐substituted aromatic amines are more thermally stable than epoxies cured with para ‐substituted aromatic amines 4. Both homolytic and heterolytic chain scission of allylic CN (CO) bonds were suggested in the literature,13, 16, 18, 23 which leads essentially to the same result (Scheme ).…”
Section: Thermal Decompositionmentioning
confidence: 87%
“…The pyrolysis behaviours of all phenolic resins in nitrogen ( Fig. 3(b DTA peak with a maximum at 301 o C. This mass loss could be due to breakdown of epoxy groups for which, in epoxy resins, a free-radical mechanism has been suggested [24]. The main decomposition reactions are represented by the second stage, which is multi-step in PH1, PH2 and PH3, as can be seen from the multiple DTG and DTA peaks, listed in Table 2(a).…”
Section: Ph Resins In Nitrogenmentioning
confidence: 96%